A Contemporary Free Verse from American and Ukrainian Readers’ Perspectives - Kulchytska, Olga; Malyshivska, Iryna (Respectus Philologicus, 2022)
The study presents an experiment aimed at discovering similarities and differences in how American and Ukrainian participants perceived contemporary free verse. Three poems were examined from the perspectives of intertextual/infratextual/intratextual context dimensions. The presence of intertextual characteristics – reflecting social reality and metaphoric content – was recognized by the majority in both groups of participants, yet across the groups, there were differences in the degree of value placed on each characteristic. Differences in views on the infratextual contexts reflect the variability of functions performed by the initial/intermediate/closing parts of the poems. As regards intratextual context dimension, there were significant similarities in the participants’ views on the imagery, in the constructed text-worlds, emotional responses, interpretations, and encountered difficulties. The analysis of the intratextual contexts of the poems indicates that some texts may drive readers’ interpretations, thus reducing the role of culture in their reception.
Keywords: free verse; intertextual/infratextual/intratextual context dimension; schema; text-world; culture